Pengaruh Teknologi Informasi, Risiko, Dan Handling Complaint Terhadap Minat Nasabah BSI Kota Palangka Raya Dalam Menggunakan Internet Banking - Muhammad Nur Iksan; Sopyan Hakim; Al Hujjah Asianingrum (Lembaga Pengembangan Kinerja Dosen, 2024)
This research responds to the development of Internet Banking technology in the banking sector. Internet banking has become an integral part of financial institutions; however, risks and handling complaints about services can influence customer interest. The research aims to analyze the influence of information technology, risk, and complaint handling on the interest of BSI customers in Palangka Raya City in using Internet Banking, both partially and simultaneously. The research method is quantitative with a survey type, involving 96 respondents determined by the lemeshow formula. Data were collected through a questionnaire, and the analysis was conducted with prerequisite tests (normality, multicollinearity, and heteroskedasticity) and using multiple linear regression analysis, T-test, F-test, and coefficient of determination in SPSS 26. The research results show that information technology and risk partially have a positive and significant effect on customer interest in using internet banking, while handling complaints do not have a significant partial effect. The F-test indicates that simultaneously information technology, risk, and complaint handling are significant for customer interest. The coefficient of determination of 0.514 shows how well these three variables explain the variation in customer interest in using internet banking.